2019
DOI: 10.1021/acs.jpcc.9b06516
|View full text |Cite
|
Sign up to set email alerts
|

On the Suitability of Raman Spectroscopy to Monitor the Degree of Graphene Functionalization by Diazonium Salts

Abstract: Raman spectroscopy is undoubtedly the most frequently used technique for universal characterization of graphene and related materials. Quantification of parameters like disorder or strain is possible through analysis of particular Raman bands. However, under certain conditions, such evaluation can be jeopardized by-sometimes hidden-convolution of more overlapping effects. In this work graphene functionalization by the common nitrobenzene diazonium salt under simultaneous biaxial tensile deformation induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
2
11
2
2
Order By: Relevance
“…A Raman map of sulphonated CVD graphene (Figure S6) showed that the I D /I G ratio was lowered at the edges, demonstrating that the chemical modifications complicate this simple metric for graphene order. This effect has previously been discussed for graphene with its basal plane modified by diazonium salts [93]. Metrics based on the relative areas of the D and G peaks, namely the average domain diameter, L A a , and average distance between point defects, L D , were more consistent.…”
Section: Resultssupporting
confidence: 59%
“…A Raman map of sulphonated CVD graphene (Figure S6) showed that the I D /I G ratio was lowered at the edges, demonstrating that the chemical modifications complicate this simple metric for graphene order. This effect has previously been discussed for graphene with its basal plane modified by diazonium salts [93]. Metrics based on the relative areas of the D and G peaks, namely the average domain diameter, L A a , and average distance between point defects, L D , were more consistent.…”
Section: Resultssupporting
confidence: 59%
“…One of the most important features of diazonium grafting is the stability of the construct; this was demonstrated by several methods including (i) thermogravimetry, where exfoliated graphene lost only 7% of its coating at 400 °C [50], (ii) spectrometric methods, where a small Raman band at 412 cm −1 was assigned to the Au(nP)-C(aryl) bond of gold nanoparticles modified by 4-nitrobenzenediazonium [51]; grafting of an aryl group on graphene [52] and carbon nanotubes [53,54] transformed an sp 2 carbon into a sp 3 , which translated into the growth of the D-band.…”
Section: The Surface Aryl Bondmentioning
confidence: 99%
“…[148,149] In plenty of reports, these graphitic derivatives have presented remarkable applications ranging from energy generation to sensing and magnetic purposes. [150][151][152][153][154]…”
Section: Other Chemical Dopingmentioning
confidence: 99%